Proyecto de inversión para la creación y comercialización de una nueva marca de ropa femenina llamada papillon en la ciudad de Guayaquil - Apolo, H. (2010)
This study is focused on determinate the viability of create a new female brand of cloth named PAPILLON in Guayaquil city. We realize that in our city the fashion industry isn’t fully develop, leaving an interesting business opportunity, created by an unsatisfied niche, as the market of women with medium and medium-high economicalsocial class who want to wear a unique and fancy cloth that they can afford. In order to accomplish the objective it is made an organizational study that obtained the main information about the human resources. Also it is developed a deep marketing and financial research that shows that the IRR is higher than MIRR, information which confirms that this is a profitable investment project